Arum palaestinum delays hepatocellular carcinoma proliferation through the PI3K-AKT-mTOR signaling pathway and exhibits anticoagulant effects with antimicrobial properties - Majdi Dwikat; Johnny Amer; Nidal Jaradat; Ahmad Salhab; Ahmad Abdal Rahim; Mohammad Qadi; Aseel Aref; Mustafa Ghanim; Haya Murad; Ali Modallal; Kawkab Shalabni (Frontiers in Pharmacology, 2023)
Background:Arum palaestinum Boiss (AP) is a wild plant in Palestine whose leaves have a long history as food and medicine in Middle Eastern countries. The current study aimed to evaluate the biological characteristics of AP flower extract, including its antimicrobial and coagulation cascade activities and its effects on anticancer molecular pathways.Methods: The antimicrobial activity of the aqueous extract of AP flowers was assessed using a microdilution assay against eight pathogens. The coagulation properties were assessed by prothrombin time (PT), activated partial thromboplastin time (aPTT), and thrombin time (TT) tests using standard hematological methods. The biological effects of AP on hepatocellular carcinoma were measured by assessing the impact of AP on cell cycle, proliferation (CFSE), apoptosis (annexin-v+/PI), and tumorigenicity (αFP and HBsAg), as well as its effects on the PI3K-AKT-mTOR molecular signaling pathway.Results: The antimicrobial screening results revealed that the aqueous extract of AP had potent antibacterial effects against P. vulgaris and E. faecium compared to ampicillin, with MIC values of 6.25, 6.25, and 18 μg/mL, respectively. Moreover, the AP aqueous extract exerted anticoagulant activity, with significant prolonged results in the aPTT and TT tests (25 μg/mL and 50 μg/mL, respectively) and slightly prolonged results in the PT test (50 μg/mL). The anticancer results indicated a delay in the cell cycle through decreased cell proliferation rates following incubation with AP fractions. The effect of the aqueous fraction was most evident in a delay in the S phase. The aqueous and DMSO fractions maintained the cells in the G2-M phase, similar to the DOX, while the flower extract in methanol accelerated the cells in the G2-M phase, suggesting that AF flower extracts may have anti-cancer properties. The aqueous extract of AP 1) reduced secretions of HCC αFP by 1.55-fold and 3.3-fold at the 50 and 100 μg/mL concentrations, respectively (p = 0.0008); 2) decreased phosphorylation in the PI3K-AKT-mTOR signaling pathway (p < 0.05); and 3) shifted cells from necrosis to apoptosis by 50% and 70% at the 50 and 100 μg/mL concentrations, respectively (p < 0.05).Conclusion: The results of this study showed the activities of the bioactive components for the treatment of infectious diseases and blood coagulation disorders, which could also be a potential therapeutic approach for delaying HCC tumorigenicity.